2011
DOI: 10.32637/orli.v41i2.48
|View full text |Cite
|
Sign up to set email alerts
|

Deteksi pepsin pada penderita refluks laringofaring yang didiagnosis berdasarkan reflux symptom index dan reflux finding score

Abstract: Background: It is estimated that more than 50% of patients with voice disorders who come fortreatment are caused by laryngopharyngeal reflux (LPR). LPR has been implicated in the etiology ofmany laryngeal disorders including subglottic stenosis, laryngeal carcinoma, laryngeal contact ulcer,laryngospasm and vocal nodule on the vocal cords. Ambulatory 24 hour double-probe (pharyngeal andesophageal) pH monitoring is the gold standard examination for diagnosing LPR, but it is still far fromideal criteria.The asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
7
0
7

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 12 publications
3
7
0
7
Order By: Relevance
“…The mean age of LPR respondents in this study was 49.20 years of age with a standard deviation of 10.95 years. This study corresponded with the results of the study by Andriani et al 11 with the age group of 41-50 years as many as 54.9% and Asyari et al 12 which found that 40% were in the 48-57 years of age group. Changes in laryngeal mucosa commonly occur in 40 years of age or older because, in females entering the menopausal age, superficial layer edema causes a decrease of laryngeal mucus production, changes also occur in the epithelial mucosa of the plica vocalis so that the mucous epithelium is thinning and the larynx is susceptible of being exposed to acidic substances which increases the occurrence of LPR.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The mean age of LPR respondents in this study was 49.20 years of age with a standard deviation of 10.95 years. This study corresponded with the results of the study by Andriani et al 11 with the age group of 41-50 years as many as 54.9% and Asyari et al 12 which found that 40% were in the 48-57 years of age group. Changes in laryngeal mucosa commonly occur in 40 years of age or older because, in females entering the menopausal age, superficial layer edema causes a decrease of laryngeal mucus production, changes also occur in the epithelial mucosa of the plica vocalis so that the mucous epithelium is thinning and the larynx is susceptible of being exposed to acidic substances which increases the occurrence of LPR.…”
Section: Discussionsupporting
confidence: 92%
“…Based on sex characteristics in this study, LPR patients were dominantly female, with a number of 23 respondents (76.7%) compared to 7 male respondents (23.3%). This findings corresponded to the study by Andriani et al 11 which found that LPR patients were mostly found in female respondents as many as 62.75%, also study by Asyari et al 12 which found as many as 76.7%, and Sarkar et al 13 which found as many as 68.2%. This was caused by hormonal factors.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…8 Another study conducted by Andriani, et al, for 51 patients with LPR, there were female (62.75%) and male (37.25%) patients. 9 The youngest age of LPR patients who sought treatment was 20 years old, and the oldest was more than 71 years. The largest age group with LPR was 41 to 50 years old, with 11 patients (26.19%) (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…The results of this study indicated that LPR cases were more frequently found in female subjects (83.3%) compared to male subjects (16.7%), with a ratio of 1.7:1. 9,10 The most frequent main complaint that brought subjects for treatment was throat clearing [11 patients (37%)]. Meanwhile, complaints of heartburn and difficulty in breathing were not the main complaints that brought subjects to come for treatment.…”
Section: Discussionmentioning
confidence: 99%